2022
DOI: 10.1007/s00423-022-02472-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative weight loss achieved by gastric balloon on peri- and postoperative outcomes of bariatric surgery in super-obese patients: a retrospective matched-pair analysis

Abstract: Background An intragastric balloon is used to cause weight loss in super-obese patients (BMI > 60 kg/m2) prior to bariatric surgery. Whether weight loss from intragastric balloon influences that from bariatric surgery is poorly studied. Methods In this retrospective, single-center study, the effects of intragastric balloon in 26 patients (BMI 69.26 ± 6.81) on weight loss after bariatric surgery (primary endpoint), postoperative complications within 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In our study, only three centres recommended preoperative weight loss by intragastric balloon placement. It was similar to the result of this article 19 , which assessed the effect of intragastric balloon placement before bariatric surgery on weight loss. The results showed that intragastric balloon placement before bariatric surgery did not have a significant impact on postoperative weight-loss outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, only three centres recommended preoperative weight loss by intragastric balloon placement. It was similar to the result of this article 19 , which assessed the effect of intragastric balloon placement before bariatric surgery on weight loss. The results showed that intragastric balloon placement before bariatric surgery did not have a significant impact on postoperative weight-loss outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, Busetto et al [ 27 ] and Zerrweck et al [ 28 ] reported decreased intraoperative conversion to open surgery, intraoperative time, and length of stay in the cohort of patients treated with IGB prior to definitive surgery. To reduce severe side effects, Hering et al [ 8 ], in line with our methods, suggested a time interval of 21 days between IGB removal and bariatric surgery, thus allowing resolution of gastric inflammation and hypertrophy. Moreover, during bridging therapy with IGB, they reported a spike of weight loss at 3 months followed by a plateau and even a slight weight regain at 5 months, suggesting a reduction of preconditioning period to reduce peri-operative complications such as perforation, nausea, vomiting, and dehydration.…”
Section: Discussionmentioning
confidence: 92%
“…In line with this study, our results showed an EWL of 39.9% and EBWL of 71.2% with a statistically significant difference compared to the group treated with medical therapy prior to surgery. Conversely, Hering et al [ 8 ] and Banks et al [ 23 ] reported comparable weight loss in patients without IGB prior to LSG, at 12 months and 24 months, respectively. However, both these studies included a very small number of patients, precluding a definitive comment on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation